PEMBUATAN VIDEO PROFIL PERUSAHAAN BERBASIS ANIMASI 3D DI PT. KRAKATAU INSAN MANDIRI - Riyan Hidayat; Hendri Gunawan; Diki Susandi (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
Multimedia as a medium of communication, information delivery, and promotion is one of the most popular technology fields. As a fields that are flexible and can be attractive, as well as pamper the human senses, multimedia can simultaneously affect humans visually, audio, and touch so that it can make consumers digest the message contained more optimally. One product that requires multimedia to improve its superiority is a company profile or profile company. In this case, PT. Krakatau Insan Mandiri seeks to introduce clearly as well as attractive to consumers through profile videos 3D animation based company. The benefits are documentation and promotional media and information about the company profile of PT. Krakatau Insan Mandiri. In making this company profile video the author uses methodologies include: Literature Study, Analysis and Design of Systems, System Implementation, System Testing, and Documentation